A comparative study of different low-cost sensible heat storage materials for solar air heating: an experimental approach. Issue 1 (31st March 2022) - Algarni, Salem; Tirth, Vineet; Saxena, Abhishek; Gupta, Parul
ABSTRACT: Among various applications of solar energy, solar air heater is a common method to fulfill the demand of hot air for space heating. In this experimental work, a low-cost solution is discussed for solar air heating. This solution deals with integration of modified models of air heaters with graphite powder, brick powder, and desert sand. These sensible heat storage materials have been filled inside a small cylindrical-shaped container to be placed over the absorber of modified heaters for performance enhancement. Total three different configurations have been developed for comparative analysis such as, configuration 1 for graphite powder testing, configuration 2 for brick powder testing, and configuration 3 for desert sand testing. Results are compared to the same design conventional heater to find out the best configuration, which shows that the configuration 1 is the best among all tested configurations. Under the configuration 1, enhanced heat transfer is observed about 541.2 W/m 2 K, thermal efficiency about 37.62%, overall heat loss about 6.71 W/m 2 K, and maximum exhaust air temperature about 41.2°C. For a better comparative analysis, configuration 1 is further compared to some other designs of solar heaters purposely for the plate temperature and thermal efficiency. Total cost of the best configuration (model) is about $59.5.